Ревизия видов рода Xanthochlorus Lw. (Diptera, Dolichopodidae) - Негробов, О.П. (Вестник зоологии, 1978)
When processing collections of the Zoological Institute of the USSR Academy of Sciences, Zoological Museum of Moscow State University and the author's own collections 7 species were determined for the USSR fauna, 5 of which are described as new for science: 1 species from the Northern Caucasus, 1 from the Northern Caucasus and England, 2 from Middle Asia and 1 species from the Primorye Territory. An identification key is compiled for species of the Xanthochlorus genus from Holarctic. It includes 10 species. The article presents the genus characteristics as well as data from literature and places of X. tenellus and X. ornatus collections within the boundaries of the USSR.